Acta Pharmacologica Sinica: Celebrating 30 years of publishing - Ding Jian (Acta Pharmacologica Sinica, 2016)
Acta Pharmacologica Sinica (APS) is now celebrating 30 years of publication. I am happy to summarize what has beenaccomplished over the past three decades. First I would like to sincerely thank the founding editor-in-chief (1980–2003), Professor Guang-sheng DING. He is well known for his strictness, tireless work ethic, and remarkable editing skills. He helped hundreds of pharmacologists bring their contributions to publication. Second I would like to thank the former editor-in-chief (2003–2007), Professor Kai-xian CHEN. Under his leadership, the impact factor of APS increased from 0.884 to 1.677. Third I want to thank each of the editorial directors, Shu-gai ZHANG, Wei-cheng WANG, Hong XIAO, and Minshu WU, as well as their editorial teams. Their great efforts have helped APS manage the editorial work efficiently and successfully and win several National Awards. Last but not least I owe a great deal of gratitude to our authors and reviewers for their strong support. Their substantial contribution to the progress of the journal cannot be overstated.